The Medea’s archetype in philosophical and literary concepts of Pascal Quignard - Мацюк, Анна Анатольевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article analyzes the Medea’s archetype in the theoretical and artistic works of the writer. This article explains how to change the Medea’s image during the author’s career. In his essays («Sex and fear», «Origin of the dance») and in his novels (Salon in Wurttemberg) writer embodies the archetype of Medea in different guises interpreting its image in the ancient way or in the psychoanalytic point of view (Schadenfreude). Trying to understand the motives of Medea's actions, Quignard emphasizes the fateful female component of the character, explaining the logic of her behavior: it is a woman, "which condemns to death the one who loves."